Btbd8 deficiency reduces susceptibility to colitis by enhancing intestinal barrier function and suppressing inflammation - Yang, Xiaoqiong; He, Zichan; Dong, Qiman; Nai, Shanshan; Duan, Xiaowei; Yu, Jiayu; Zhao, Nannan; Du, Xiaoling; Chen, Lingyi (Frontiers in Immunology, 2024)
Introduction BTBD8 has been identified as a susceptible gene for inflammatory bowel diseases (IBD). However, the function of BTBD8 in normal development and IBD pathogenesis remains unknown. Methods We administered drinking water with 3% dextran sodium sulfate (DSS) to wild-type (WT) and Btbd8 knockout (KO) mice for seven consecutive days to induce IBD. Subsequently, we further examined whether Btbd8 KO affects intestinal barrier and inflammation. Results We demonstrated that Btbd8 deficiency partially protects mice from DSS-induced IBD, even though no obvious phenotypes were observed in Btbd8 KO mice. Btbd8 deletion leads to strengthened tight junctions between intestinal epithelial cells, elevated intestinal stem cell activity, and enhanced mucus layer. All these three mechanisms work together to improve the intestinal barrier integrity in Btbd8 KO mice. In addition, Btbd8 deficiency mitigates inflammation by reducing the expression of IL-1β and IL-6 by macrophages. Discussion Our studies validate the crucial role of Btbd8 in IBD pathogenesis, and reveal that Btbd8 deficiency may ameliorate DSS-induced IBD through improving the intestinal barrier integrity, as well as suppressing inflammatory response mediated by macrophages. These findings suggest that Btbd8 could be a promising therapeutic target for the treatment of IBD.